2020
DOI: 10.1111/caim.12395
|View full text |Cite
|
Sign up to set email alerts
|

Digital innovation in law firms: The dominant logic under threat

Abstract: This paper focuses on the impact of digitalization in the legal industry. The legal industry is highly institutionalized and has for long been unaffected by external changes. This has enabled the development of a strong institutional logic that has dictated homogeneous practices in law firms and limited their room for innovation. However, this seems about to change. Through a qualitative case study of the Swedish legal industry, this paper shows that new practices, enabled by digitalization, challenges common … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 59 publications
1
18
0
Order By: Relevance
“…Still, research within both professions also indicates that commercialization, globalization and digitalization influence both accountants' and lawyers' work (see e.g. Cooper & Robson, 2006;Francis, 2020;Hanlon, 1998;Kronblad, 2020;Lander et al, 2012;Skjølsvik et al, 2017). During data collection, we were therefore intrigued to explore to which extent patterns of differences or similarities would emerge.…”
Section: Methodsmentioning
confidence: 99%
“…Still, research within both professions also indicates that commercialization, globalization and digitalization influence both accountants' and lawyers' work (see e.g. Cooper & Robson, 2006;Francis, 2020;Hanlon, 1998;Kronblad, 2020;Lander et al, 2012;Skjølsvik et al, 2017). During data collection, we were therefore intrigued to explore to which extent patterns of differences or similarities would emerge.…”
Section: Methodsmentioning
confidence: 99%
“…This second perspective addresses the conversation on how digital transformation challenges professional boundaries and jurisdictions and also generates new institutional actors and actor constellations Kronblad, 2020). These processes relate to a long-standing theme within institutional research, namely how professions shape institutions (DiMaggio & Powell, 1983;Ruef & Scott, 1998).…”
Section: Digital Transformation Professional Projects and New Institu...mentioning
confidence: 99%
“…Established, traditional professions (e.g., doctors, lawyers) have considerable control over their jurisdictions (i.e., defining what and how work is done, including defining appropriate values and norms as well as criteria for entering the profession and making a career) yet are facing increasing pressure and challenges from digital technologies that consequently change the institutional context of their work Oborn et al, 2021;Smets, Morris, von Nordenflycht, & Brock, 2017). For example, Kronblad (2020) found in the context of the Swedish legal industry that legal tech start-ups utilizing digital technologies are questioning the dominant professional logic through value-based or subscription-based pricing; however, many traditional law firms remain reluctant to change. Björkdahl and Kronblad (2021) find in a study of the digitalization of court processes in response to the COVID-19 crisis that judges may be more willing to participate in digitalization processes if court managers not only emphasize efficiency gains but also how digitalization fits judges' professional ethos (i.e., arriving at fair verdicts).…”
Section: Digital Transformation Professional Projects and New Institu...mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has shown that some professions are more inclined to embrace digital technologies, while others are more reluctant ( Susskind and Susskind 2015 ). Resistance to changing work practices is particularly evident in contexts that are simultaneously highly institutionalized and highly professionalized ( Kronblad 2020 ). In the highly institutionalized and professionalized medical field, prior research has, for example, reported on difficulties in transforming work practices by using electronic medical record (EMR) systems (instead of paper-based records).…”
Section: Introductionmentioning
confidence: 99%